The development and influence of the Qing Dynasty’s royal meal during the Qianlong period - Huang, Xinyi; Suffian Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Food culture development reflects a country’s growth to a certain extent. Qing Dynasty’s royal meals represent this period’s food culture. As the Qing Dynasty became stronger than before, it peaked during the Qianlong period. This development reflects the Qing Dynasty’s political, economic, and cultural development and occupies an essential position in the history of food culture. However, the development and influence of royal meals during the Qianlong period have yet to be comprehensively analyzed and sorted out. Therefore, this study aims to explore the development process of royal meals during the Qianlong period and the positive and negative effects on politics, economy, and culture. This article adopts qualitative research, including literature survey and analysis methods to classify and organize the literature and historical archives collected from Chinese historical archives and libraries. Through sorts out and analysis of the development of royal meals during the Qianlong period of the Qing Dynasty, it found that the development of royal meals during the Qianlong period was accompanied by the development of national strength and the personal preferences of the emperor, and the development of royal meals also brought various influences. This study is of great value for studying ancient Chinese culinary culture and provides a new perspective for studying the social development during the Qianlong period of the Qing Dynasty. At the same time, it also reminds us that while vigorously developing the cultural industry, we must consider its impact on society.